Soluble syndecan‐1 (SDC1) serum level as an independent pre‐operative predictor of cancer‐specific survival in prostate cancer. Issue 11 (7th April 2016) - Szarvas, Tibor; Reis, Henning; vom Dorp, Frank; Tschirdewahn, Stephan; Niedworok, Christian; Nyirady, Peter; Schmid, Kurt W.; Rübben, Herbert; Kovalszky, Ilona
Abstract : BACKGROUND: PSA‐screening detects many cases of clinically non‐aggressive prostate cancer (PC) leading to significant overtreatment. Therefore, pre‐operatively available prognostic biomarkers are needed to help therapy decisions. Syndecan‐1 (SDC1) is a promising prognostic tissue marker in several cancers including PC but serum levels of shedded SDC1‐ectodomain (sSDC1) have not been assessed in PC. METHODS: A total of 150 patients with PC were included in this study (n = 99 serum samples, n = 103 paraffin‐embedded samples (FFPE), n = 52 overlap). SDC1 protein expression and cellular localization was evaluated by immunohistochemistry (IHC), while sSDC1 serum concentrations were measured by ELISA. Serum sSDC1 levels were compared to those of MMP7, which is known to be a protease involved in SDC1 ectodomain‐shedding. Clinico‐pathological and follow‐up data were collected and correlated with SDC1 tissue and serum levels. Disease (PC)‐specific (DSS) and overall‐survival (OS) were primary endpoints. RESULTS: Median follow‐up was 167 months in the serum‐ and 146 months in the FFPE‐group. SDC1‐reactivity was higher in non‐neoplastic prostate glands compared to PC. In addition, cytoplasmatic, but not membranous SDC1 expression was enhanced in PC patients with higher Gleason‐score >6 PC ( P = 0.016). Soluble SDC1‐levels were higher in patients with Gleason‐score >6 ( P = 0.043) and metastatic disease ( P = 0.022) as well as in patients with progressed disease treated with palliative transurethral resection ( P = 0.002). In addition, sSDC1 levels were associated with higher MMP7 serum concentration ( P = 0.005). In univariable analyses, only sSDC1‐levels exhibited a trend to unfavorable DSS ( P = 0.077). In a multivariable pre‐operative model, high pre‐operative sSDC1‐level (>123 ng/ml) proved to be an independent marker of adverse OS ( P = 0.048) and DSS ( P = 0.020). CONCLUSIONS: The present study does not confirm the prognostic relevance of SDC1‐IHC. The significant higher sSDC1 serum levels in advanced cases of PC, suggest that SDC1 shedding might be involved in PC progression. Additionally, high sSDC1‐level proved to be an independent factor of adverse OS and DSS in a multivariable pre‐operative model, making evaluation of sSDC1‐levels a promising tool for pre‐operative risk‐stratification and/or therapy monitoring. Prostate 76:977–985, 2016 . © 2016 Wiley Periodicals, Inc.